Prison Folk Poetry: The Barone Trilogy - Burns, Richard (Ethnologies, 1993)
Data for this paper are three poems collected by a convict at a southeast Texas prison farm. The poems are about his past acquaintance, a fellow convict known as Johnny Barone. The first poem was composed as a birthday gift to its subjects, the second by Barone himself, and the third by the prisoner collecting them, who, even though the protagonist still lived, titled it “The Epitaph of Johnny Barone”, completing a trilogy. As a set, these poems represent traditional forms in which prisoners express their attitudes toward crime, punishment, the penal System, the past and the present.